Exploring culturally relevant leadership learning : case studies for leadership educators - Guthrie, Kathy L.; Pacheco, Derrick Raphael (Emerald Publishing Limited, 2025)
Exploring Culturally Relevant Leadership Learning: Case Studies for Leadership Educators offers a comprehensive collection of case studies that delve into the eight critical aspects of the culturally relevant leadership learning model. These aspects include identity, capacity, efficacy, and the cultural dimensions of historical legacy of inclusion and exclusion, compositional diversity, psychological dimensions, behavioral dimensions, and organizational structure. Through meticulously curated case studies set in both curricular and co-curricular spaces, this book provides readers with a rich tapestry of diverse contexts and environments. These case studies serve as invaluable tools for leadership educators, helping them develop a broader and more inclusive perspective on leadership learning. Whether used in classrooms, workshops, or personal study, these stories offer practical insights and real-world applications that can enhance the journeys of those seeking to understand and practice leadership in a culturally relevant way. Centering culturally relevant leadership learning is not only crucial for educators striving to create inclusive learning spaces but also for students learning to lead in diverse contexts and with diverse people. As the field of leadership education evolves beyond traditional and canonical theories, this book encourages educators to explore various contexts and perspectives. With contributions from forty diverse educators, practitioners, and scholars in higher education, these case studies highlight the benefits of educational stories in supporting learners to gain insights from various situations, perspectives, and contexts. Exploring Culturally Relevant Leadership Learning is a guide to fostering inclusive leadership practices and enriching the educational experiences of future leaders.
Includes index.
Keywords: Leadership -- Case studies.; Education -- Leadership.; Educational systems and structures.; Educational strategies and policy.; elektronické knihy; electronic books